The competent classroom aligning high school curriculum, standards, and assessment ; a creative teaching guide - Zmuda, Allison; Tomaino, Mary (Series on school reform, 2001)
Describes the cross-disciplinary journey of two high school teachers trying to align curriculum, assessment, and performance standards in their classrooms. With a focus on the importance of constantly inspiring students, the authors troubleshoot issues surrounding content standards, instructional objectives, and the aims of curriculum.